Climatic features as a factor for development of tourism in the Republic Of Macedonia - Mijalce Gjorgievski; Dejan Nakovski (UTMS Journal of Economics, 2014)
The development of tourism in general besides the anthropogenic factors have important natural features expressed through all their features, and one of them is the climate. When we talk about tourism in rural areas as an alternative form of tourism, we have to look at the climate characteristics from a different perspective, because alternative forms of tourism have a seasonal nature, and i.e. it is a specific form of tourism that is practiced throughout the year. Therefore it is not good to have extreme temperatures and climate both in the positive and the negative terms in the area in which tourism is going to be practiced. Temperature extremes might be suitable for primary or so-called mass forms of tourism such as summer оr winter tourism, which largely depends on the number of sunny hours, air temperature, amount of snowfall, number of days with snow etc. But this is not the case when it comes to rural tourism, because it's practiced throughout the whole year and it's not dependent on the parameters that were given above, but this form of tourism requires an inviting climate all year round. It is therefore important to understand the basic climatic characteristics where the natural environment is an important factor for the development of tourism in the rural areas in the country.
Keywords: Q26; 330; climate; rural tourism; temperature; seasons; altitude zones